Drying technique for local foodstuffs using the uop8-mkii electric dryer: Case of mango and okra in the Guera region of Chad - Said, Said Zakaria; Nimir, Yacoub Nassian; Mbaitelbe, Koularambaye; Hissein, Hissein Adoum (International Journal of Chemical and Process Engineering Research, 2026)
Drying is one of the most widely used methods for preserving food products in rural areas. Drying staple foods, particularly mango and okra, in the Guera region of Chad using a UOP8-MKII electric dryer is part of an approach to enhancing their value. The method preserves perishable foodstuffs, especially in Chad, where post-harvest losses constitute a significant portion of agricultural production. The experiment was conducted in the Thermal Laboratory of the Polytechnic University of Mongo in Chad. The technique employs a UOP8-MKII material dryer, which allows precise control of drying parameters. Food samples were subjected to varying temperatures, thicknesses, and surface areas to analyze the influence of these parameters on drying kinetics. The results show that high temperatures accelerate drying but can alter organoleptic quality if poorly controlled. A thin layer facilitates faster drying, resulting in better water diffusion. The surface area also significantly influences the rate of moisture removal. Okra dries more slowly than mango at the same thickness due to its fibrous structure. These findings are in partial agreement with previous studies, where only temperature and thickness were primarily examined. The study highlights the importance of the drying surface, which is rarely considered but highly influential. The results were compared with those of earlier research to confirm this hypothesis. This research provides a better understanding of the key factors in drying local products. It opens prospects for optimizing drying processes to reduce post-harvest losses and increase the value of Chad’s agricultural products.